Wireless structural health monitoring system for cranes - Ng, Gerard-Christian Zhi Li. (2010)
This proposed project aims to design a wireless real time structural health monitoring (SHM) system for tower crane structures that dominate construction sites to assure their safety. This research will focus on the stability of crane structures when subjected to operational and wind loadings. It will also examine the effects of structural damage to the crane’s global behaviour. The crane structure will be linked and monitored by vibrating wire strain gauges and Linear Variable Displacement Transducers (LVDT). All changes in stress or any other static parameters of selected parts of the crane structure can be detected immediately. Thus catastrophic failure of the structure can be averted.